ANALISIS MINAT DAN BAKAT MAHASISWA PENJASKESREK TAHUN 2017 - Tuti Sarwita (Jurnal Penjaskesrek, 2018)
This research is aimed to inform Apasajakah interest and talent of Student / Programmaster of STKIP BBG in Penjasesrek year 2017. The formulation of problem in this research is to see how Student Interest and Talent in Penjaskesrek STKIP BBG 2017. In this research using quantitative descriptive approach. The subjects of this study were obtained by using Total Sampling technique. The subjects of this study were all Students / Penjaskesrek STKIP BBG anggaktan 2017. Data collection techniques used in this study using the instrument Questionnaire. Based on the results of the study From the Analysis results bahwasannya interests and talents of students penjaskesrek STKIP Bina Bangsa Getsempena class of force 2017, in the field of sports varies. Can be seen from the analysis that the interests and talents of students in soccer as much as 26 people from 51 students where the results can dipersentasekan 51%. In the sports section berragabulutangkis students who are interested as much as 5 people with a percentage of 10%. In basketball, the number of students who follow as many as 2 people with a percentage of 4%. Likewise in cator sports cabag, evening and karate students who each followed as many as 2 people with a percentage of 4% as well. On Volly sporting students are interested as many as 8 people with a percentage of 16%. And at the sports branches of Monthai, Silat, Tekwando and the art of singing each of the 1 students who are interested with the percentage of 2%, and the art of each voice as much as 1 person with a percentage of 2%. Abstrak Penelitian ini bertjuan untuk mengtahui apasajakah minat dan bakat Mahasiswa/wi Programstudi Penjaskesrek STKIP BBG tahun 2017. Rumusan masalah dalam penelitian ini adalah untuk melihat bagaimana Minat dan Bakat Mahasiswa/wi dalam Penjaskesrek STKIP BBG tahun 2017. Dalam penelitian ini menggunakan pendekatan deskriptif kuantitatif. Subjek penelitian ini diperoleh dangan menggunakan tehnik Total Sampling. Subjek penelitian ini adalah seluruh Mahasiswa/i Penjaskesrek STKIP BBG anggaktan 2017. Tehnik pengumpulan data yang digunakan dalam penelitian ini menggunakan instrumen Angket. Berdasarkan hasil peneltian Dari hasil Analisis bahwasannya minat dan bakat mahasiswa program studi penjaskesrek STKIP Bina Bangsa Getsempena angkatan 2017, dalam bidang olahraga bervariasi. Dapat dilihat dari hasil Analisis bahwa minat dan bakat mahasiswa dalam cabang olahraga sepak bola sebanyak 26 orang dari 51 mahasiswa dimana hasil tersebut dapat dipersentasekan 51%. Pada cabang olahragabulutangkis mahasiswa yang berminat sebanyak 5 orang dengan persentase 10%. Pada cabang olahraga basket, jumlah mahasiswa yang mengikuti sebanyak 2 orang dengan persentase 4%. Begitu juga pada cabag olahraga cator, Petang dan karate mahasiswa yang masing-masing mengikuti sebanyak 2 orang dengan persentase 4% juga. Pada cabang olahraga Volly mahasiswa yang berminat sebanyak 8 orang dengan persentase 16%. Dan pada cabang olahraga Monthai, Silat, Tekwando dan seni tarik suara masing-masing 1 orang mahasiswa yang berminat dengan persentase 2%, dan seni suara masing – masing sebanyak 1 orang dengan persentase 2%. Kata Kunci: Minat Bakat